Participation of divalent cation transporter DMT1 in the uptake of inorganic mercury. (4th May 2015) - Vázquez, M.; Vélez, D.; Devesa, V.; Puig, S.
Abstract: Mercury (Hg) is found in food in various chemical forms, which differ in terms of accumulation, transport, and toxicity. Although methylmercury (CH3 Hg) is the predominant mercury species in the diet, contributed mostly by seafood products, there is also a contribution of inorganic mercury [Hg(II)] from vegetables, cereals, and seafood products. The main pathway for exposure to mercury is oral, and therefore the gastrointestinal mucosa is the first barrier that the contaminant meets when it enters the systemic circulation. However, the transport mechanisms responsible for the process of mercury absorption are not known. The aim of this study is to evaluate the possible participation of divalent metal transporter 1 (DMT1) in Hg(II) intestinal uptake. For this purpose, we have used various complementary approaches. We have studied mercury acquisition in a Saccharomyces cerevisiae strain expressing murine DMT1 . Moreover, we have evaluated the effect of a reduction of DMT1 expression in Caco-2 cells, by means of small interfering RNA and of treatment with hepcidin, on mercury uptake and transport. The results show that expression of the transporter DMT1 in yeast produces an increase in Hg(II) accumulation. Furthermore, a decrease in the levels of DMT1 mRNA in Caco-2 cells in various stages of differentiation leads to a reduction in cellular accumulation and apical-basolateral transport of Hg(II). These data point clearly to the mediation of the divalent cation transporter DMT1 in the entry of Hg(II) into the intestinal epithelium.